Soft-output equalization and TCM for wireless personal communication systems. - Yue Chen
This paper investigates the use of a maximum a posteriori probability (MAP) algorithm to realize soft-output equalization in a concatenated equalization and trellis-coded modulation (TCM) decoding-based wireless communication system. Specifically, we first begin with a general MAP algorithm and then focus on studying Bahl's (1974) MAP and Lee's (1974) MAP algorithms. We then propose a modified version of Lee's MAP algorithm which is much simpler than the original, in terms of complexity, and is more practical. In particular, a very simple channel estimation method which employs orthogonal training sequences is proposed. In order to improve the system performance, equal-gain combining and selection diversity are also considered. Finally, we compare the performance of the MAP algorithm-based equalization with our previously proposed equalization scheme, which combines decision feedback equalization and TCM
Keywords: Bahl's MAP algorithm; DFE; Lee's MAP algorithm; PCS; TCM; Channel estimation method; Complexity; Concatenated equalization; Decision feedback equalization; Decoding; Equal-gain combining; Frequency-selective Rayleigh fading channels; High speed data transmission; Maximum a posteriori probability; Multipath propagation; Orthogonal training sequences; Selection diversity; Soft-output equalization; System performance; Trellis-coded modulation; Wireless personal communication systems